KAJIAN TENTANG KESIAPAN DAN PERAN ANAK SMA BERKEBUTUHAN KHUSUS DALAM RESPON DARURAT BENCANA: STUDI KASUS DI SKH YDW 03 KOTA TANGERANG [STUDY ON THE READINESS AND ROLE OF SENIOR HIGH SCHOOL STUDENTS WITH SPECIAL NEEDS IN EMERGENCY DISASTER RESPONSE: A CASE STUDY AT SKH YDW 03 TANGERANG CITY] - Hasrian, Hasrian; Rahmat, Hayatul Khairul (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study aims to examine the readiness and role of senior high school students with special needs in responding to disaster emergencies. The scope of the study includes understanding, skills, and social support received by special needs students in disaster situations. The method used is a combination of quantitative surveys and qualitative interviews with students, teachers, and parents from several disaster-prone schools. The findings of the study show that despite facing various physical and cognitive limitations, special needs students have the potential to actively contribute if provided with appropriate training and support. The findings emphasize the importance of an adaptive curriculum and effective communication methods to enhance their preparedness. The main conclusion of this study is that involving special needs children in disaster training and response can strengthen both individual and community resilience.